2013
DOI: 10.1080/08916152.2012.719066
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Fouling in Experimental Micro Heat Exchangers—Optical and Thermal Investigations

Abstract: The intention of this work is the basic investigations of the fouling behavior in micro heat exchangers. Therefore fouling experiments with calcium carbonate (CaCO 3 ) in an experimental micro heat exchanger were carried out and observed with a digital microscope. The investigations included local temperature measurements confirmed by computational fluid dynamics simulation as well as optical visualization of the fouling process inside the microchannels. The detected fouling resistances R f were in the range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The results confirm the findings in [16] that cleaning in place of micro heat exchangers is possible and that the investment of acid-resistant surfaces could be beneficial if this type of cleaning is required. Note that it was observed that cleaning in place (CIP) was enhanced through the bypass flow below the fins between the micro-channels, which can be attributed to the clamped construction of the experimental micro heat exchanger.…”
Section: Cleaning Progresssupporting
confidence: 92%
See 2 more Smart Citations
“…The results confirm the findings in [16] that cleaning in place of micro heat exchangers is possible and that the investment of acid-resistant surfaces could be beneficial if this type of cleaning is required. Note that it was observed that cleaning in place (CIP) was enhanced through the bypass flow below the fins between the micro-channels, which can be attributed to the clamped construction of the experimental micro heat exchanger.…”
Section: Cleaning Progresssupporting
confidence: 92%
“…(16)); k 1 , k 2 , and k 3 are coefficients determined from fitting Eq. (16) to the different cleaning curves:…”
Section: Cleaning Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, removal of crystals was not observed. In later experiments, Mayer et al 24 observed via optical investigation an uneven distribution of the deposits in the parallel channel arrangement which had developed during the experiment. This was due to an inhomogeneous distribution of the heat flux and to a fouling-induced maldistribution of the fluid flow in the parallel channels.…”
Section: Crystallization Foulingmentioning
confidence: 94%
“…Therefore, new strategies for early fouling detection, as well as methods for fouling mitigation, suitable for microcomponents, are required. Nevertheless, microstructured devices have proven beneficial in academic and industrial applications .…”
Section: Introductionmentioning
confidence: 99%